2021
DOI: 10.1007/s42001-021-00132-w
|View full text |Cite
|
Sign up to set email alerts
|

Computational courtship understanding the evolution of online dating through large-scale data analysis

Abstract: In this work, we examine the mate preferences and communication patterns of male and female users of the online dating site eharmony over a decade to identify how attitudes and behaviour have changed over this time period. While other studies have investigated disparities in user behaviour between male and female users, this study is unique in its longitudinal approach. We analyze how men and women differ in their preferences for certain traits in potential partners and how those preferences have changed over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Profile information was obtained through a collaboration with eharmony UK, who stipulated that the user data analyzed here and in Study 2 cannot be made freely available. The dataset comprised information taken from 149,440 website profiles which had previously been used to explore dating preferences and messaging behaviors (Dinh et al, 2018). In all cases, users were living in the United Kingdom, heterosexual, and not currently in a relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Profile information was obtained through a collaboration with eharmony UK, who stipulated that the user data analyzed here and in Study 2 cannot be made freely available. The dataset comprised information taken from 149,440 website profiles which had previously been used to explore dating preferences and messaging behaviors (Dinh et al, 2018). In all cases, users were living in the United Kingdom, heterosexual, and not currently in a relationship.…”
Section: Methodsmentioning
confidence: 99%
“…This is further complicated by the fact that online dating often encourages users to prioritize qualities (e.g., height, income) that are poor indicators of what it will be like to interact with someone in the flesh (Frost et al, 2008). Many online dating sites have since started using more sophisticated machine learning algorithms to predict users' preferences from implicit forms of feedback (Dinh et al, 2021).…”
Section: Compatibility Matching On Online Dating Sitesmentioning
confidence: 99%
“…However, this approach assumes that compatibility comes from matching people who are similar in desirability, when online daters are also known to engage in aspirational mate pursuit by seeking out the most desirable partners (Bruch & Newman, 2018;Dinh et al, 2021).…”
Section: Dating Apps and Collaborative Filteringmentioning
confidence: 99%
“…Alluding to Maslow's hierarchy of needs, entrepreneurs saw the profit potential in exploiting human's innate need to form social connections. Thereby transforming online dating into a highly lucrative market; as Michael Norton noted (as cited in Dinh et al, 2022), "finding a romantic partner is one of the biggest problems that humans face" (p. 402). Companies are investing billions of dollars in creating an immersive world for consumers, drowning individuals in an array of advertisements through billboards, displays on public transits, or targeted ads, proclaiming that dating apps are the modern cupid.…”
Section: Introductionmentioning
confidence: 99%
“…2). As a result of the extensive advertisement and the conditions of the modern world, dating apps are becoming increasingly popular, making them some of the most used apps on the market; as Dinh et al (2022) reported, there is a 70% annual growth rate in the usage of online dating apps by Americans. In addition, some predict that "by 2040 seventy percent of individuals will have met their significant other online" (Anderson, 2016, as cited in Manta et al, 2019, p. 209).…”
Section: Introductionmentioning
confidence: 99%